A tacit-knowledge perspective on networked learning - Dohn, Nina Bonderup (Proceedings of the International Conference on Networked Learning, 2012)
Within the field of networked learning, many researchers take their point of departure in "practice" theories, i.e. theories which stress that the meaning of actions, artefacts, and procedures are bound up with concrete contexts of activity. Important representatives of such "practice theories" are activity theory, expansive learning, and social learning theory. In this article I flesh out a "practice" view of knowledge. I integrate insights from Wittgenstein, phenomenology and situated learning to formulate a view of knowledge as tacit, situated, relational, practical, context-dependent, embodied doing. Building on this view of knowledge, I argue that insights and understandings from one context have to be resituated, transformed, and reactualized to be brought into use in other contexts. I also point out that a main task for educators today is to challenge their students to resituate their tacit, practical understandings across the different contexts they participate in - and to support them in learning to do so. Networked learning activities may play important roles here because they can be designed as "mediator activities" which are characterized by catalyzing the coupling of primary contexts, whilst not aiming at the attainment of educational ends themselves. Such mediator activities have their anchorage in the settings to be coupled, not in the coupling. In contrast, networked learning activities designed to be a "place" for the pursuit of educational goals tend to become stand-alone activities which seem somewhat ’abstract’ and unrelated to ’what is really at stake’ for the participants, i.e. what shows up for them as significant on the background of their tacit practical embodied understanding.